Living justice: Catholic social teaching in action - Massaro, Thomas (Rowman & Littlefield Publishers, 2023)
"This book explains the development, sources, and methods of Catholic social teaching and describes its major themes and applications. It brings the tradition up to date, with the inclusion of the major social teaching of Pope Francis"--